EV Fast Charging, an Enabling Technology. (1st January 2015) - Botsford, Charles; Edwards, Andrea
Abstract : Mass adoption of electric vehicles (EVs) would revolutionize transportation, provide a path for penetration of renewables onto the grid, and greatly reduce reliance on oil. However, obstacles remain before this vision can be realized. Many "early EV adopters" have chosen high cost EVs with large battery packs that greatly reduce the specter of range anxiety. Many other EV adopters have chosen the lower cost, lower size battery pack route, which comes with a lower driving range per charge. What if an EV auto manufacturer could offer a low cost EV to capture the mainstream car buyer, but didn't have to sacrifice range? The ten-minute fast charging paradigm may be the long-term answer to overcoming this obstacle to mass adoption.